Experimental validation of a phaseless, non‐redundant planar spiral scanning for antenna characterisation - Florindo Bevilacqua; Amedeo Capozzoli; Claudio Curcio; Francesco D’Agostino; Flaminio Ferrara; Claudio Gennarelli; Rocco Guerriero; Angelo Liseno; Massimo Migliozzi; Yiannis Vardaxoglou (IET Microwaves, Antennas & Propagation, 2023)
Abstract An effective, probe‐compensated, phaseless Near‐Field‐Far‐Field (NF–FF) transformation technique with planar spiral scanning is presented. The phase retrieval problem is solved by a quadratic inverse process, whose data are the voltage squared amplitudes of the NF samples acquired on two scanning surfaces. The available information on the antenna under test and on the scanning geometry are used to provide efficient representations for both the unknowns and the data, thus improving the accuracy and reliability of the technique. Furthermore, disconnected apertures are dealt with by adopting two different sets of prolate spheroidal wave functions to represent the aperture fields. Experimental results are reported to assess the effectiveness of the proposed approach. A drastic reduction (about 90%) of the required NF samples, as compared to standard λ/4 measurements (λ being the wavelength), is observed. Aggregating the measurements on the two scanning surfaces, the technique uses less samples even when compared to the case of complex, λ/2 measurements performed on a single surface. Our approach exhibits an accuracy comparable to that achieved when adopting complex measurements with non‐redundant sampling or classical, λ/2 plane‐rectangular NF–FF transformations.